The changing macroeconomic information content of aggregate earnings - Kottimukkalur, Badrinath; Nallareddy, Suresh; Venkatachalam, Mohan (Review of Accounting Studies, 2025)
We examine the dynamic nature of the information content of aggregate earnings. Specifically, we examine how changes in supply elasticity affect the relation between aggregate earnings and future inflation. Using total capacity utilization to capture supply elasticity, we find that aggregate earnings are more informative about inflation when the supply is inelastic. This finding aligns with the investment demand hypothesis—higher aggregate earnings drive increased investment, pushing inflation higher, when supply is relatively inelastic. Furthermore, when we consider market outcomes such as three-month Treasury yields and aggregate stock returns, the role of supply elasticity pervades. That is, we find that aggregate earnings are more informative for market outcomes primarily when supply is inelastic. Finally, the relation between aggregate earnings and gross domestic product (GDP) also varies with the economy’s supply elasticity. Our findings highlight supply elasticity as a critical factor in interpreting the macroeconomic signals in aggregate earnings.